Peran Penyuluh Pertanian Lapangan dan Tingkat Partisipasi Anggota Kelompok Wanita Tani Dalam Program Pekarangan Pangan Lestari (P2L) (Studi Kasus Pada Kelompok Wanita Tani Desa Pujorahayu Kecamatan Negeri Katon Kabupaten Pesawaran) - Antika, Lucky Lindu; Syarief, Yuniar Aviati; Nurmayasari, Indah; Listiana, Indah (Fakultas Pertanian, Universitas Lampung, 2022)
The performance of agricultural extension officer (Indonesian: Petugas Penyuluh Pertanian Lapangan, thereafter called PPL) is closely related to the participation of the members of Farmer Women Group (Indonesian: Kelompok Wanita Tani, thereafter called KWT) in sustainable food yard (Indonesian: Pekarangan Pangan Lestari, thereafter called P2L) program. It makes the role of agricultural extension officer need attention recalling its significant effect on its target. The objective of research is to find out the role of PPL in the implementation of P2L program activity, the participation of KWT members in P2L program, and factors relevant to the participation of members in P2L program. This research took place in Pujorahayu Village, Negerikaton Sub District, Pesawaran Regency. In this study, data was collected in December 2021-January 2022. This research used a case study method with descriptive quantitative approach. The result of research shows that the role of PPL in the implementation of P2L belongs to high category. The participation of KWT Sekar Asri members is classified into high category, and the rest into medium category. The factors relevant to the participation of KWT Sekar Asri members are: age, formal education level, occupation, number of family member, yard land width, and role of PPL. . Keywords: KWT, the Role of Agricultural Extension Officer, Participation of KWT members